Challenges during cardiac arrest in pregnancy - Korneel Berteloot; Marc Sabbe (Resuscitation Plus, 2025)
A 36-year-old woman at 23 weeks and 3 days of gestation experienced a witnessed cardiopulmonary collapse. Bystander cardiopulmonary resuscitation (CPR) was initiated immediately. After advanced life support, she was transferred under mechanical CPR to a hospital for extracorporeal membrane oxygenation (ECMO). There, a delayed perimortem caesarean section (PMCS) was performed. Consideration to initiate ECMO following the PMCS was ultimately discontinued due to extensive intra-abdominal haemorrhage and the elapsed time of over one hour since the collapse. A full body computed tomography (CT) scan following ROSC revealed bilateral pulmonary embolisms and grade 4 liver laceration with active bleeding due to mechanical CPR. Despite the prolonged duration of cardiac arrest (69 min) and significant metabolic derangements, the patient had a favourable recovery and was discharged after 42 days with a good neurological outcome. This case illustrates the challenges of timely perimortem caesarean section in out-of-hospital cardiac arrest, where guidelines recommend performing the procedure within 4 min of maternal collapse. It also highlights the risks associated with mechanical chest compression devices.